Urban Solid Waste Management in Karachi, Pakistan: Urban Solid Waste Management in Karachi, Pakistan - Mahmood, Hajra; Khan, Muhammad Moiz (International Journal of Economic and Environmental Geology, 2019)
Karachi is the largest metropolitan city of Pakistan with a population of 207,774,520 (Statistics, 2017). Ironically, a megacity of a developing state has its drawbacks and discrepancies in solid waste mechanism being one of them. Karachi has always been the center of businesses and government offices since independence, first as capital of Pakistan and later as a provincial capital. This study evaluates the importance of solid waste management for an urban city such as Karachi, and the steps which have been taken by the successive governments to fulfill the demands of this growing megapolis since independence. In this study, models of solid waste management adopted by different cities will be analyzed and a suitable model for Karachi will be proposed. Needless to say, Karachi has the potential to become an eco-friendly city by adopting the public private partnership. In short, the civil society’s role is of paramount importance.